2023
DOI: 10.1128/spectrum.02663-21
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Approach Reveals Intercellular Heterogeneity in Phage-Producing Capacities

Abstract: Phages produce offspring by hijacking a cell's replicative machinery. Previously, it was noted that the variation in the number of phages produced by single infected cells far exceeded cell size variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In order to find a robust feature that is less dependent on the specific choice of the parameters, we focused on the features robustly observed for a large range of f τ and f β . However, in reality, f τ and f β should positively correlate [5,13].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In order to find a robust feature that is less dependent on the specific choice of the parameters, we focused on the features robustly observed for a large range of f τ and f β . However, in reality, f τ and f β should positively correlate [5,13].…”
Section: Discussionmentioning
confidence: 95%
“…1. In reality, a positive correlation between the increase of the latency time and the increase of the burst size has been observed [5,13].…”
Section: M1 -Simple Model Of Linmentioning
confidence: 98%
See 1 more Smart Citation
“…However, more work is needed to identify the mechanisms underlying variability, including those that impact other viral traits. For example, while correlations between latent period and burst size have been observed, with phage strains with longer latent periods having larger burst sizes [13], recent studies suggest that variation in (induced) lysis time does not contribute to observed burst size variability [46,47]. Caution in the interpretation of multi-cycle response curves is required, as viral traits often depend on host growth rate which can vary in experimental timescales [12].…”
Section: Discussionmentioning
confidence: 99%
“…The study found a positive correlation between lytic activity and burst size, while a negative correlation was observed between lytic activity and both the latent phase and the rising phase. The magnitude of the burst size holds significant importance as it directly correlates with the quantity of viral particles generated, hence indicating the possibility for further cellular infections (Kannoly et al, 2023). After conducting the single-step experiment, it was observed that the lytic Psa phages had a growth curve with an Sshape, which was distinguished by a substantial burst size and a brief latency period.…”
Section: Lytic Activitymentioning
confidence: 99%